WORLD TRENDS IN THE DEVELOPMENT OF EXPERT AND ANALYTICAL ACTIVITY IN ASSESSMENTS AND CRITERIA - Sembiyeva, L.M.; Tazhbenova, G.; Orynbekova, G.A.; Z., Z.; Petrov, A.M. (Scientific Journal of Pedagogy and Economics, 2020)
World experience indicates that the implementation of expert analysis, largely, affects the level of high-quality management decisions, as well as the level of executive decision-making in the budget and financial sphere. In addition, these measures contribute to increasing the degree of responsibility, transparency and accountability in the activities of state bodies. The authors studied the world practice of conducting expert and analytical activities, evaluating the effectiveness of the application of expert and analytical activities, developing methodological recommendations for conducting similar work in the Republic of Kazakhstan. The study examined the experience of four countries, such as Germany, the USA, Great Britain and the Russian Federation. The expert-analytical activity of VOGA in all the countries listed, except for the Russian Federation, is not legally regulated. There are no relevant norms in the laws governing the activities of VOGA. In all of the above countries, except for Russia, expert and analytical activities are not methodologically regulated. The rules, procedural standards, and audit requirements do not provide for a methodology for expert analysis. The study of documents arising from the activities of the SAIs of the above countries, such as audit reports, analytical reports, annual reports (except for the Russian Federation) allows us to conclude that expert analysis in the above countries is carried out to a greater extent during the performance audit. The experience of the abovementioned countries, as well as the study of ISSAI standards related to the implementation of the performance audit, indicates that the full-scale implementation of the performance audit can lead to the absence of the need for additional expert analytical work. Since in accordance with ISSAI 300, the performance audit itself delivers a new information, knowledge and value.